Enhanced iodide transport after transfer of the human sodium iodide symporter gene is associated with lack of retention and low absorbed dose - Haberkorn, Uwe; Kinscherf, Ralf; Kübler, Wolfgang; Eisenhut, Michael; Altmann, Annette (Gene therapy, 2003)
Transfer of the sodium iodide symporter (hNIS) has been proposed as a new principle of cancer gene therapy. Using clinically relevant doses of 131I for the treatment of NIS-expressing prostate carcinoma cells, we investigated the kinetics and the absorbed doses obtained in these tumors. hNIS-expressing cell lines accumulated up to 200 times more iodide when compared to wild-type cells. However, a rapid efflux of the radioactivity (80%) occurred during the first 20 min after replacement of the medium. In rats, the hNIS-expressing tumors accumulated up to 20 times more iodide when compared to contralateral transplanted wild-type tumors. After 24 h and doses of 550, 1200 or 2400 MBq/m2 hNIS-expressing tumors lost 89, 89 and 91% of the initial activity, respectively. Dosimetric calculations showed that 1200 MBq/m2 resulted in 30.5 Gy (wild-type tumor 0.150.1 Gy) and 2400 MBq/m2 resulted in 3.10.9 Gy (wild-type tumor 0.260.02 Gy). Although transduction of the hNIS gene induces iodide transport in rat prostate adenocarcinoma a rapid efflux occurs, which leads to a low absorbed dose in genetically modified tumors. With regard to a therapeutic application additional conditions need to be defined leading to iodide trapping.